Associations of tobacco and alcohol use with sexual behaviors among adolescents in 59 countries: a population-based study - Jiahong Sun; Yongliang Zhu; Liu Yang; Chuanwei Ma (BMC, 2024)
Abstract Background Sexual behaviors, particularly risky sexual behavior, has become a serious public health concern among adolescents worldwide, presenting a substantial obstacle to the prevention of sexually transmitted infections, including human immunodeficiency virus (HIV). However, there is limited research using consistent and standardized methodology to examine associations between tobacco and alcohol use frequency and both total and risky sexual behaviors among adolescents. We aimed to examine the association between tobacco and/or alcohol use with both total and risky sexual behaviors among adolescents worldwide. Methods Data were collected from the Global School-based Student Health Survey, which comprised 211,847 adolescents aged 12-17 years from 59 countries. The frequency of tobacco or alcohol use during the past 30 days was categorized as 0, 1-2, 3-5, 6-9, or ≥ 10 days. Tobacco and alcohol use were also categorized as non-use, tobacco use alone, alcohol use alone, and combined use. Multi-variable logistic regression analysis was used to examine both the independent and combined associations of tobacco and alcohol use with total and risky sexual behaviors. Results Compared with no tobacco use, the odds ratio of engaging in sexual intercourse increased with the frequency of tobacco use from 1 to 2 days to ≥ 10 days (total: 2.03 [95% confidence interval 1.47-2.81] to 3.98[2.63-6.03]; risky: 2.43[1.75-3.38] to 4.21[3.26-5.42]), as well as with the frequency of alcohol use. Overall, combined users had greater likelihood of both total and risky sexual behaviors than tobacco users alone, alcohol users alone, and non-users. Similarly, the association between risky sexual behaviors and tobacco use alone was more pronounced among adolescent girls (vs. adolescent boys), as were those of risky sexual behaviors with alcohol use alone among younger adolescents aged 12-14 years (vs. aged 15-17 years) and with tobacco and/or alcohol use among adolescents in the Western Pacific region (vs. Regions of Africa and Americas). Conclusions Our findings suggest independent and combined associations between tobacco and/or alcohol use with sexual behaviors among adolescents, with variations across age, sex, and WHO region.